1996
DOI: 10.1210/mend.10.7.8813730
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Igf1 gene null mutation on mouse reproduction.

Abstract: Both sexes of adult mice homozygous for a targeted mutation of the Igf1 gene, encoding insulin-like growth factor 1, are infertile dwarfs (approximately 30% of normal size). The testes are reduced in size less than expected from the degree of dwarfism but sustain spermatogenesis only at 18% of the normal level. The epididymides are overall nearly allometric to the reduced body weight, but the distal regions of the duct, vas deferens, seminal vesicles, and prostate are vestigial. Despite the mutational impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
202
0
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(219 citation statements)
references
References 0 publications
15
202
0
2
Order By: Relevance
“…The importance of IGF1 in uterine biology was shown by studies within IGF1-null mutant mice that were shown to have hypotrophic uteri with minimal development of the myometrium (20), which is consistent with studies showing that 125 I-IGF1 bound to cells in the myometrium (17). Similarly, using organ culture of immature uterus, IGF1 was shown to potentiate the proliferative response principally in the myometrium but also in the stroma (16).…”
Section: Discussionsupporting
confidence: 72%
“…The importance of IGF1 in uterine biology was shown by studies within IGF1-null mutant mice that were shown to have hypotrophic uteri with minimal development of the myometrium (20), which is consistent with studies showing that 125 I-IGF1 bound to cells in the myometrium (17). Similarly, using organ culture of immature uterus, IGF1 was shown to potentiate the proliferative response principally in the myometrium but also in the stroma (16).…”
Section: Discussionsupporting
confidence: 72%
“…In light of these data, we decided to examine whether IGF-IR activation in vivo regulates the phosphorylation of the Crk proteins and their interaction with paxillin, previously identified as having high affinity binding sites for the Crk SH2 domain (22,26). The development of the uterus is regulated by the IGF system acting in a paracrine manner, with uterine growth severely retarded in mice in which the Igf1 gene has been deleted by homologous recombination (19). IGF-IR mRNA is expressed at all stages of uterine development in both the myometrium and endometrium, while IGF-I mRNA exhibits a more restricted pattern of expression that is dependent on the stage of development (19).…”
Section: Discussionmentioning
confidence: 99%
“…The IGF-IR is known to have a critical role in mediating the effects of estrogen on the development of the uterus in the rodent. The development of the uterus is severely impaired in mice homozygous for a deletion of the IGF-I gene (19), while estrogen treatment of ovariectomized rats stimulates the tyrosine phosphorylation of the IGF-IR ␤-subunit and IRS-1 (20).…”
mentioning
confidence: 99%
“…Like gonadotropins, GH is secreted by the anterior pituitary where Plag1 is expressed. In addition, GH has a direct effect on the IGF system that regulates reproductive physiology (Baker et al 1996, Zhou et al 1997, Hull & Harvey 2000, Pitetti et al 2013, Zhou et al 2013, Wolfe et al 2014 and that has been systematically identified as a target of Plag1. However, Plag1 KO mice do not seem to have a lower number of hypophyseal GH cells .…”
Section: Possible Mechanisms Linking Plag1 To Reproductive Physiologymentioning
confidence: 99%